James Edward Huheey (1935 - 2020). In memory of an unsual chemist - Ortega-San-Martin, Luis (2020)
This short note summarises the unusual characteristics of the author of one of the best-known books in the area of inorganic chemistry: James E. Huheey. This American chemist was so passionate about herpetology that he excelled in both sciences and gained respect from all his peers.